2013
DOI: 10.5194/bg-10-2683-2013
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a 39-year continuous atmospheric CO<sub>2</sub> record from Baring Head, New Zealand

Abstract: Abstract. We present an analysis of a 39-year record of continuous atmospheric CO2 observations made at Baring Head, New Zealand, filtered for steady background CO2 mole fractions during southerly wind conditions. We discuss relationships between variability in the filtered CO2 time series and regional to global carbon cycling. Baring Head is well situated to sample air that has been isolated from terrestrial influences over the Southern Ocean, and experiences extended episodes of strong southerly winds with l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 62 publications
5
50
0
Order By: Relevance
“…This enhanced uptake in ocean biogeochemical models is consistent with the expected uptake of −0.05 Pg C yr −1 decade −1 of the Southern Ocean sink (Le Quéré et al, 2007), due to the increasing atmospheric CO 2 concentration. Conversely, the inversions are more consistent with a reduction in the strength of the Southern Ocean sink reported by Le Quéré et al (2007), but the range is 4050 A. Lenton et al: Sea-air CO 2 fluxes in the Southern Ocean large across inversions (−0.06 to 0.08 Pg C yr −1 decade −1 ) and previous work has shown that the inversion trends are likely quite sensitive to atmospheric CO 2 data quality, with atmospheric CO 2 gradients being close to measurement uncertainty (Stephens et al, 2013). This suggests that linear trends in model output over periods less than 20 yr are unlikely to provide a statistically meaningful statement about the very small changing rate of Southern Ocean CO 2 uptake.…”
Section: Southern Ocean 44-75 • Ssupporting
confidence: 79%
See 1 more Smart Citation
“…This enhanced uptake in ocean biogeochemical models is consistent with the expected uptake of −0.05 Pg C yr −1 decade −1 of the Southern Ocean sink (Le Quéré et al, 2007), due to the increasing atmospheric CO 2 concentration. Conversely, the inversions are more consistent with a reduction in the strength of the Southern Ocean sink reported by Le Quéré et al (2007), but the range is 4050 A. Lenton et al: Sea-air CO 2 fluxes in the Southern Ocean large across inversions (−0.06 to 0.08 Pg C yr −1 decade −1 ) and previous work has shown that the inversion trends are likely quite sensitive to atmospheric CO 2 data quality, with atmospheric CO 2 gradients being close to measurement uncertainty (Stephens et al, 2013). This suggests that linear trends in model output over periods less than 20 yr are unlikely to provide a statistically meaningful statement about the very small changing rate of Southern Ocean CO 2 uptake.…”
Section: Southern Ocean 44-75 • Ssupporting
confidence: 79%
“…Law et al, 2008). Analyses of long-running atmospheric CO 2 time series in the Southern Hemisphere and model simulations suggest that it may not be possible to robustly detect a slowdown in the Southern Ocean sink 4040 A. Lenton et al: Sea-air CO 2 fluxes in the Southern Ocean from atmospheric CO 2 measurements at present (Stephens et al, 2013). Furthermore, ocean observations also suggest the changes in the sink efficiency may not be zonally uniform for the Southern Ocean .…”
Section: Biogeosciencesmentioning
confidence: 99%
“…A much larger fraction of the variability in CO 2 is caused by exchanges with the land biosphere; this is true even in regions remote from direct land biospheric influences, such as the high latitudes of the Southern Hemisphere (e.g., Stephens et al, 2013). An atmospheric constraint on oceanic processes can be derived by combining measurements of atmospheric CO 2 and O 2 / N 2 ratios to compute atmospheric potential oxygen (APO).…”
Section: Atmospheric Potential Oxygen: Definition Simulation and Obsmentioning
confidence: 99%
“…The first method named SI is based on "steady intervals" (Lowe et al, 1979;Stephens et al, 2013). Steady intervals which are considered as baseline conditions are defined by a standard deviation being lower or equal than 0.3 ppm for 6 or more consecutive hours.…”
Section: Other Statistical Data Selection Methods For Comparisonmentioning
confidence: 99%